Study on Causes & Control of Cracks in a Structure (International Journal of Innovative Research in Computer Science & Technology, 2022)
Our main aim of the project is to know the  causes and preventive measures of cracks in buildings. A  crack is a complete or incomplete separation of concrete in  two or more parts by breaking or fracturing. It is a inherent  feature in concrete which cannot be prevented but controlled  and reduced. Structural Cracks are a common occurrence in  all types of buildings. To ensure the longevity of the  structure, engineers are often required to look into their  causes and carry out suitable repairs and remedial measures.  For repairs and remedies to be effective, it is essential that  the engineer should have a proper understanding of various  causes of occurrence of cracks. For investigating the causes  it is necessary to observe carefully the location, shape, size,  depth, behavior and other characteristics of the cracks, and  to collect information about specifications of the job and  time of construction. It is also necessary for the engineer to  keep track of when the cracks first came to notice.
Keywords: Cracks; Grouting; Shrinkage; Structural failure; Stresses